SPEED-STRENGTH RELATIONSHIP BETWEEN ROWING ON ERGOMETER AND CLEAN PULL EXERCISE - Oleg Hristov (Journal of Applied Sports Sciences)
Speed-strength qualities are significant for obtaining high power, especially in sports such as rowing. There are few surveys quoted in literature on multi-joint movements with increasing load in the training and competitive range of intensity where the speed-strength qualities are traced. In our research, we aim to make a comparative analysis of speed-strength qualities with increasing load in two multi-joint exercises: rowing on rowing ergometer and the clean pull strength exercise. The research was conducted among rowers (n=7; age - 16.28 ± 1.11 years; weight - 73.12 ± 7.63 kg; height - 186.27 ± 7.20 cm). The test on a rowing ergometer was performed with Concept II Model C, and the data were processed with the system BioRowTech. The data from the strength exercise were recorded and processed with the system GymAwareCloud. Regression equations were worked out for the speed-strength qualities: in clean pull exercise – peak force R2 =0.52 and average force R2 =0.76; in rowing on ergometer – peak force R2 =0.72 and average force R2 =0.56. We found out that in both exercises the mean power reached was almost identical (in rowing = 692.28 W, in clean pull = 609.42 W), but in rowing it is on account of higher velocity and less force.